2020
DOI: 10.1111/jvim.15771
|View full text |Cite
|
Sign up to set email alerts
|

The effect of freeze‐thaw cycles on determination of immunoreactive plasma adrenocorticotrophic hormone concentrations in horses

Abstract: Background: Determination of plasma adrenocotrophic hormone (ACTH) concentration (endogenous or thyrotropin-releasing hormone [TRH] stimulation test) is the most commonly used diagnostic test for pituitary pars intermedia dysfunction (PPID) in horses. Because ACTH is unstable, samples often are frozen to be shipped to laboratories or to allow for batch analysis of research samples. However, the effect of multiple freeze-thaw cycles on equine ACTH is unknown.Objective: To determine the effects of multiple free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…31 with an interassay coefficient of variation of 4.8% and an intraassay coefficient of variation of 5.4% as previously described. 32 Not all horses were tested every month. Additional data recorded included sex, age, and body condition score (BCS).…”
Section: Methodsmentioning
confidence: 99%
“…31 with an interassay coefficient of variation of 4.8% and an intraassay coefficient of variation of 5.4% as previously described. 32 Not all horses were tested every month. Additional data recorded included sex, age, and body condition score (BCS).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma ACTH concentrations were determined using a validated chemiluminescent immunoassay (Immulite 1000, Siemens Diagnostics) 28 . Samples were analysed in a single batch within 1 month of the conclusion of the study period and subjected to one freeze–thaw cycle to minimise the potential variability that can occur with multiple freeze–thaw cycles 29 . Plasma cortisol concentrations were determined using a validated radioimmunoassay (Coat‐A‐Count, Siemens Diagnostics) 30,31 .…”
Section: Methodsmentioning
confidence: 99%
“…27,33,34 The literature also reports compensatory increases in energy intake after a period of caloric restriction, despite PO administration of glucose, as opposed to nonfasted individuals. 35 This finding suggests that pro- Lastly, it has been suggested that ACTH 40,41 and cortisol 42 recovery decreases minimally with storage time and number of freeze-thaw cycles. Studies evaluating the stability of glucagon in humans suggest it is a very stable hormone, with minimal changes at room temperature for 3 days 43 and 5 days at 4 C. 44 The recovery of glucagon also has been shown to improve with the addition of EDTA/aprotinin 43,45 and DPP-IV inhibitors.…”
Section: Discussionmentioning
confidence: 87%